ADAPTIVE PID BASED SPEED TRACKING CONTROL OF DC MOTOR - Husain, M.H; Ahmad, F.; Che Hasan, M.H. (Journal of Mechanical Engineering and Technology (JMET), 2023)
This paper presents a study on the speed tracking control of DC Motor that is develop by using an Adaptive Proportional-Integral-Derivative (APID) control structure. APID controller is used due to the ability to solve the drawback of conventional PID controller. DC motor system and proposed controller was simulated using MATLAB-Simulink software. Several tests such as step function, sine wave function and saw tooth function were used to examine the performance of the proposed controller. Several speeds input was used to evaluate the performance of APID controller. The result show that the proposed control structure can achieve targeted speed control with a good response. The DC Motor test rig are used to investigate in real time experiment for the ability of the proposed controller structure by comparing simulation APID with experiment APID controller. The result show that the proposed control structure proves to be able to track the desire speed with acceptable error.